Analisis Pertumbuhan Ekonomi Dan Pengembangan Sektor Potensial di Kota Banjarmasin Tahun 2013 s.d 2017 - Yahya, Dedy; Wardhana , Ali (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2022)
This study aims to (1) find out the primary and non-base sectors in Banjarmasin City and (2) find out the right policy strategy for developing potential sectors in Banjarmasin City. This study uses analytical tools to determine the basis and non-base sectors through the calculation of Location Quotient and Shift Share, then for development strategies through descriptive analysis, with the uses of secondary data in the form of gross regional domestic product according to employment at constant prices. The results showed seven basic sectors, namely the electricity and gas procurement sector; Construction; Financial and insurance services; Real estate; Company services; Educational services; Health services, and social activities. And for the sector being developed is the electricity and gas procurement sector as the leading sector, as well as the water supply, waste management, waste, and recycling sectors as potential sectors.